A Multi-professional Approach for Transition of Care at Discharge in Hyperglycemic Inpatients with COVID-19: A Single Center Study - Castellano, Elena; Gaviglio, Donatella; Pellegrino, Micaela; Gianotti, Laura; Magro, Giampaolo; Tassone, Francesco; Baffoni, Claudia; Sibbono, Renza; Attanasio, Roberto; Boriano, Alberto; Borretta, Giorgio (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: The discharge from the hospital of insulin-treated hyperglycemic patients is always challenging. This is even more so in patients requiring glucocorticoid treatment, such as those with COVID-19. Patients and Methods: A retrospective monocentric study of 23 inpatients was conducted with newly diagnosed or already known diabetes mellitus (DM) who were naïve to insulin treatment, and who were hospitalized with COVID-19 in non-critical settings and then discharged. Patients were followed up for one month after discharge for the management of insulin treatment by a multi-professional team through phone consultations. Results: Insulin prescriptions at discharge were 24.6 ± 14 U/day injected in 2 ± 1.5 daily shots. A mean of three phone consultations was required. One month later, the mean insulin reduction was 1.5 ± 1.3 shots and 6 ± 5 U/day. All patients reached their glycemic target without hypoglycemic events, drop-outs, or readmissions. Conclusion: This study demonstrates the feasibility, efficacy, and safety of a multi-professional approach through telemedicine for managing DM patients after discharge during COVID-19.
Keywords: insulin requirement